The cardiorespiratory fitness and cardiovascular risk among security officers within a University - Wong, Jackson (Universiti Malaysia Sarawak (UNIMAS), 2013)
Physical fitness is important in most high physically demanding jobs especially in the armed forces and security services. However, physical fitness in these jobs are often neglected due to the prolong interval of low physical demand followed by a sudden spike of high physical demand when needed. This research used a cross-sectional survey to explore cardiorespiratory fitness, cardiovascular risk factors and the relationships that exist between physical activity, cardiorespiratory fitness and cardiovascular risk factors among security officers in UNIMAS using the International Physical Activity Questionnaire Short-fonn (lPAQ-S), the YMCA 3 minutes physical fitness test and blood test for fasting sugar and cholesterol levels. In particular, this study aimed to determine the socio-demographic characteristics, cardiovascular risk factors, level of cardiorespiratory fitness and the relationship between cardiorespiratory fitness, cardjovascular risk factors and sociodemographic characteristics among the university security officers. A total of 100 respondents participated in this study. The rate percentage of the respondents who were found to be smokers was 53.1%; high blood pressure was 34.7%; deranged cholesterol levels was 37.8%; deranged blood glucose was 37.8% and abnormal BMI was 76.5%. There were 74.4% respondents (n=73) with more than two risk factors; 23.5 respondents (n=23) with one risk factor and 2 (n=2.1) had no risk factors. Two cardiovascular risk factors which were found to have statistically significant associated with cardiorespiratory fitness were fasting blood glucose (X2 = 6.082, df= 2, P < 0.05) and physical activity (X2 =9.337, df= 1, P < 0.05). In conclusion, physical inactivity and the risk of hypertension, diabetes and high cholesterol levels were existing problems among the security officers where all except for high BP were above the figures reported by NHMS III. Mo-st of the security officers were also found to have poor cardiorespiratory fitness. Both employee and employers should take an active role in planning a healthy working environment and schedule, with compulsory regular annual medical examination and full gymnasium university utilization to monitor and maintain physical fitness and high physical activity amongst the security officers.